Penilaian Kapabilitas Tata Kelola TI Perguruan Tinggi dengan Framework COBIT 5 dan ITIL V3 - Roni Yunis; Elly Elly (Fakultas Informatika, 2021)
The intention of doing the research is to formulate an assessment model of higher education IT governance capability, by integrating two frameworks, namely COBIT 5 and ITIL V3. Currently, there is no academic organization that has fully formulated a measurement model for IT governance capabilities that can be adopted to manage both governance and services. To achieve the goal of this research will be measured needs to be done using the COBIT 5 framework as a tool to get the capability level of IT governance. Next will measure the level of capability of existing IT services with ITIL V3. The proposed model was obtained from the measurement activities using COBIT 5 domain, namely EDM02, EDM03, APO01, APO04, APO07, APO12, and APO13. After measuring, sevens processes that lead to IT governance and IT services are evaluated, namely evaluating, directing, and overseeing the delivery of benefits and managing IT service portfolios and optimizing risks; manage IT management frameworks and carry out seven steps to improve IT processes; managing innovations in higher education; managing human resources; managing capacity; manage risk and manage information security. The model generated from this research is expected to serve as a best practice for Universities in Indonesia in implementing Good IT Governance